Efektivitas Senam Kesegaran Jasmani Indonesia Bersatu 2018 Terhadap Peningkatan Kebugaran Jasmani Siswa Di Sd Negeri Mintaragen 2 Kota Tegal (Indonesian Journal for Physical Education and Sport, 2022)
The purpose of this study was to determine the effectiveness of gymnastics physical fitness Indonesia Bersatu 2018 to improve student fitness. This study is an experimental study, the subjects of this study are students of Class IV and V in SD Negeri Mintaragen 2 Kota Tegal with a total sample of 62 students. Design in this study using pre-test and post-test group. Treatment in this study is by Gymnastics physical freshness Indonesia Bersatu 2018, while for the test using TKJI. Data analysis techniques using descriptive statistics, normality test with one way anova, chi-square test, and difference test with T test. This study memeproleh average value with the results of pretest son daughter 12.89, pretest son 13.53, pretest daughter 12.43 and posttest son daughter 14.73, posttest son 15.31, posttest daughter 14.73. With the percentage increase between pretest to posttest son has an increase of 13.1%, for the presentation of the increase in daughter has an increase of 16%. The conclusion of this study that shows that the United Indonesia physical fitness Gymnastics 2018 is effective for improving students physical fitness.